2009
DOI: 10.1177/0888406409346149
|View full text |Cite
|
Sign up to set email alerts
|

Concept Mapping as a Research Tool to Evaluate Conceptual Change Related to Instructional Methods

Abstract: Concept maps are commonly used in a variety of educational settings as a learning aid or instructional tool. Additionally, their potential as a research tool has been recognized. This article defines features of concept maps, describes the use of pre- and postconcept maps as a research tool, and offers a protocol for employing concept maps as an effective research tool. To illustrate the viability of concept maps as a research tool, specific steps and examples are provided from a study that used concept maps t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 15 publications
(24 reference statements)
0
21
0
6
Order By: Relevance
“…Wilson, Nash and Earl (2010) explored the impact of collaboration between teachers and students with language learning difficulties on teachers' thinking about vocabulary teaching through the use of CM as measurement of teacher knowledge and understanding. Similarly, Miller et al (2009) employed CM as a pre-test and a post-test to empirically measure teachers' conceptual growth after participation in a multimedia case-based instruction and recommended CM as a credible and effective research tool. Cabellero, Moreira and Rodriguez (2008) found that CM had great pedagogical potential for mental modelling to explore teachers' internal representations and their possible evolutions.…”
Section: Related Literature In Teacher Educationmentioning
confidence: 99%
“…Wilson, Nash and Earl (2010) explored the impact of collaboration between teachers and students with language learning difficulties on teachers' thinking about vocabulary teaching through the use of CM as measurement of teacher knowledge and understanding. Similarly, Miller et al (2009) employed CM as a pre-test and a post-test to empirically measure teachers' conceptual growth after participation in a multimedia case-based instruction and recommended CM as a credible and effective research tool. Cabellero, Moreira and Rodriguez (2008) found that CM had great pedagogical potential for mental modelling to explore teachers' internal representations and their possible evolutions.…”
Section: Related Literature In Teacher Educationmentioning
confidence: 99%
“…En esta última sesión, para la elaboración de los mapas post, se volvieron a presentar los mismos conceptos orientativos presentados en la sesión 1. (Fernández y Rodríguez, 1995;Miller et al, 2009;Rivadulla et al, 2015). Por otra parte, estos criterios de valoración llevan asociado un sistema de puntuación, de manera que han generado 3 escenarios de evaluación (bajo, medio, alto), como puede verse en la Tabla 1 y sus correspondientes ejemplos en las Figuras 1, 2 y 3.…”
Section:  Sesión 3 Mapas Conceptuales (Post Posteriores)unclassified
“…Esta herramienta ofrece la posibilidad de construir, guardar y modificar mapas conceptuales de una manera sencilla, pudiendo agregar recursos digitales de todo tipo (documentos, imágenes, vídeos, enlaces web,…) a los conceptos del mapa para enriquecer el contenido digital del mismo, pero también permite a los usuarios colaborar a distancia en la construcción de sus mapas, publicarlos para que cualquier persona pueda acceder a ellos en Internet y hacer búsquedas en la Web relacionadas con el mapa. El uso educativo de los mapas conceptuales se fundamenta inicialmente en la teoría del aprendizaje significativo (González García, 2008) y también se conecta con la visión constructivista sobre los procesos de enseñanza y aprendizaje (Novak y Cañas, 2005;Miller, Koury y Fitzgerald, 2009), donde los conocimientos previos del alumno pueden interpretarse en términos de esquemas cognitivos que evolucionan, se reestructuran y se enriquecen con el aprendizaje. Tales esquemas no solo se caracterizan por la cantidad de conocimientos que contienen, sino también por su nivel de organización interna, es decir, por las relaciones que se establecen entre los conocimientos que se integran en un mismo esquema y por el grado de coherencia entre dichos conocimientos.…”
Section: Antecedentesunclassified